An Outbreak of Aeromonas salmonicida in Juvenile Siberian Sturgeons (Acipenser baerii) - Esther Vázquez-Fernández; Blanca Chinchilla; Agustín Rebollada-Merino; Lucas Domínguez; Antonio Rodríguez-Bertos (Animals, 2023)
Aeromonas salmonicida is one of the major threats to world aquaculture, causing fish furunculosis and high mortality rates in cultured fish, particularly salmonids. Although Aeromonas spp. is a thoroughly studied pathogen, little is known regarding aeromoniasis in sturgeons. After a mortality outbreak, four juvenile sturgeons (Acipenser baerii) were submitted for autopsy and tissue samples were collected for histopathological and microbiological studies. The external examination revealed size heterogenicity, skin hyperpigmentation and reduced body condition of sturgeons. Within the abdominal cavity, mild hepatomegaly and splenomegaly were observed, as well as generalized organic congestion. Histology revealed severe multifocal haemorrhagic and ulcerative dermatitis, mainly localized in the dorsal and latero-ventral areas of fish. The histological study also showed moderate to severe inflammation of gills and organic lesions compatible with septicaemia. Bacterial isolates were identified as Aeromonas salmonicida subsp. salmonicida using MALDI-TOF MS and PCR. Overall, the lesions first described here are consistent with those previously reported in other cultured fish species and contribute to a better understanding of the pathogenesis of Aeromonas salmonicida subsp. salmonicida in the Siberian sturgeon, aside from providing new diagnostic tools for bacterial diseases impacting the fast-growing industry of caviar.